The problem of urban violations in Algeria-Field Study: The Case of Boufarik Municipality (Blida Province) - Akhelfhoum, Karim (Journal of Architecture and environment of child, 2022)
The phenomenon of urban violations in Algeria has witnessed a remarkable development starting from the late seventies of the last century, and the increase in residential buildings without being subject to regulatory controls and standards related to urban planning tools is attributed to many factors, the most important of which are: the housing crisis, the increasing migrations towards cities, and urban centers resulting from the unbalanced development between Rural and urban areas. The main question that arises in this research paper is how to deal with various urban issues, the most important of which is the problem of urban irregularities, so that we seek through research to diagnose the phenomenon, and this is by studying its forms and factors of its emergence; And the reasons for its spread in light of the challenges of producing environmentally friendly cities, and the municipality of Boufarik appears as a model to highlight the phenomenon of urban violations in Algeria.